Hubungan Pola Makan dengan Kejadian Stunting pada Balita Usia 24-59 Bulan di Wilayah Kerja Pueskesmas Kajhu Kecamatan Baitussalam Kabupaten Aceh Besar - Aida Zahra; Yusrika Yusrika; Nurul Sadah (Lembaga Pengembangan Kinerja Dosen, 2026)
Representing a pervasive global and national health concern, stunting reflects prolonged nutritional deprivation that affects early childhood development irrespective of gender. To evaluate this phenomenon, a cross-sectional quantitative analysis was executed to examine the empirical association between dietary regimens and stunting incidents among toddlers aged 24–59 months in the operational zone of the Kajhu Public Health Center, Baitussalam, Aceh Besar. Deploying a structured ordinal questionnaire for primary data collection from May 20 to June 11, 2025, this investigation involved 169 strategically sampled respondents extracted from a total population of 952 children. Univariate and bivariate analytical frameworks, specifically the Chi-Square test, were employed for data elucidation. The empirical assessment demonstrated that 62.1% (n=105) of the participants were stunted, whereas 37.7% (n=64) exhibited normal growth metrics; furthermore, inappropriate feeding regimens were observed in 57.4% (n=97) of the cohort compared to 42.6% (n=72) with adequate dietary compliance. Based on the inferential statistical test, a significance value of p = 0.000 (p < 0.05) was obtained, necessitating the rejection of the null hypothesis and confirming a robust correlation between childhood nutritional intake configurations and stunting prevalence. These empirical findings underscore the critical urgency for intensified parental oversight and strategic dietary optimizations as primary preventative measure.